Human Capital Management Adopted by SLB-D YPAC Bandung - Junianto, Dani; Bangun, Yuni Ros (Journal of Business and Management, 2015)
Abstract- The objective of the study was to determine the extent to which the SLB-D YPAC BANDUNG had adopted the Human Capital Management (HCM) practices. The HCM practices that were explored include: resourcing, strategies, talent management, learning and development, and performance and reward management strategies. The study used the case study design that was based on a target population of 30 people in the school. A sample of twenty nine (29) staff, just excluding the headmaster was selected. Data collection instruments used by the study were an interview guide and a questionnaire. However, a substantial amount of data was collected through documentary analysis. A response rate of 100% was achieved by the questionnaire technique, while one of the four interviewee sampled were interviewed. Both content and quantitative analysis were used to analyze data which was then presented in frequency tables, percentages, rank ordering, and mean scores and standard deviation. Overall, the findings of the study indicate that the organization has implemented HCM practices, but to a negligible extent. Some of the HCM practices adopted by the organization include: : effective communication channel, equipping them with competencies required to achieve the organizational goal, and Explaining organization mission, vision, and value to the staff. However, the rest of the practices have either not been adopted or are adopted to a negligible extent. The study also suggests that there is need for further research, particularly in the area of human capital measurement, since the organization didnâ€™t use any tool available and the continued applied research for when the organization had implemented a clear human capital measurement.Â Keywords: Human capital management, competitive advantage, human capital advantage, intangible assets and human capital planning.Category: Performance Management, Human Resource Management